Fertility, Household Structure, and Parental Labor Supply: Evidence from Rural China - Hongbin Li; Junjian Yi; Junsen Zhang (Institute for the Study of Labor (IZA), 2015)
This paper tests the effects of fertility on household structure and parental labor supply in rural China. To solve the endogeneity problem, we use a unique survey on households with twin children and a comparison group of non-twin households. The ordinary least squares estimates show a negative correlation between fertility and parental labor supply. Using twinning as a natural experiment, we do not find evidence on the negative effects of fertility on parental labor supply. By contrast, we find that the twinning-induced increase in fertility enhances significantly the coresidence of grandparents. The results remain robust when we use the Chinese 1990 population census. We suggest that the negative effects of fertility on parental labor supply are mitigated by the childcare provided by grandparents. Our results have important implications for population and public childcare policies.
Keywords: J13; J18; J22; O10; 330; fertility; parental labor supply; household structure